Functionalization of zirconia ceramic with fibronectin proteins enhanced bioactivity and osteogenic response of osteoblast-like cells - Aung, Lwin Moe; Lin, Jerry Chin-Yi; Salamanca, Eisner; Wu, Yi-Fan; Pan, Yu-Hwan; Teng, Nai-Chia; Huang, Haw-Ming; Sun, Ying-Sui; Chang, Wei-Jen (Frontiers in Bioengineering and Biotechnology, 2023)
To overcome the genuine bioinert properties of zirconia ceramic, functionalization of the surface with the bioactive protein fibronectin was conducted. Glow discharge plasma (GDP)-Argon was first used to clean the zirconia surface. Then allylamine was treated at three different powers of 50W, 75W, and 85W and immersed into 2 different fibronectin concentrations (5µg/ml and 10µg/ml). After surface treatment, irregularly folded protein-like substances were attached on the fibronectin coated disks, and a granular pattern was observed for allylamine grafted samples. Infrared spectroscopy detected C-O, N-O, N-H, C-H, and O-H functional groups for fibronectin treated samples. Surface roughness rose and hydrophilicity improved after the surface modification, with MTT assay showing the highest level of cell viability for the A50F10 group. Cell differentiation markers also showed that fibronectin grafted disks with A50F10 and A85F10 were the most active, which in turn encouraged late-stage mineralization activity on 21d. Up-regulation of osteogenic related mRNA expression from 1d to 10d can be observed in RT-qPCR data for ALP, OC, DLX5, SP7, OPG and RANK biomarkers. These physical and biological properties clearly indicate that an allylamine and fibronectin composite grafted surface significantly stimulated the bioactivity of osteoblast-like cells, and can be utilized for future dental implant applications.